Rabbits or Refuse? Landfill Use and Relevance as a Food Source for an Increasing Wintering Population of the Red Kite - Íñigo Vicente-Hernández; Félix Martínez; Guillermo Blanco (Diversity, 2023)
Household waste landfills represent a huge source of trophic resources for opportunistic and versatile wildlife species. Among them, the red kite (Milvus milvus) is one of the most endangered in Europe. Several studies have pointed out the importance of landfills as a source of food for this species during the wintering season, but the information on the frequency, seasonal and daily patterns of use, and age of red kites that exploit this food source is still insufficient to understand their actual role in conservation. In this study, we evaluated the patterns of use of household waste by overwintering red kites in southeastern Madrid, central Spain. The results showed the constant presence of relatively low numbers (<30 on average) and a reduced hourly inflow and outflow of red kites throughout the day and during the whole winter period in the studied landfill. A higher proportion of juveniles was found in the landfill than in the overall wintering population. Pellet analysis clearly shows that the diet of red kites is dominated by the wild rabbit (Oryctolagus cuniculus), which is quantitatively very relevant compared to household waste obtained from the landfill. This suggests a relatively low quantitative importance of landfills as foraging grounds for the increasing population of wintering red kites in the study area. Instead, the high regional density of wild rabbits attracts large numbers of red kites that can eventually use landfills as a non-optimal last-resort foraging option, owing to the predictability of household waste, especially for juveniles. The continuous presence of red kites in landfills likely influences an uninformed positive perception about their relevance to the conservation of the wintering population, despite risks there faced, such as collision, electrocution, and intoxication. Future research is needed to assess in depth the influence of wild rabbits in Spain on the habitat use and global population dynamics of red kites.